EKSPLORASI PENGARUH TINGKAT PENDAPATAN DAN LOCUS OF CONTROL TERHADAP IMPULSIVE BUYING DENGAN LITERASI KEUANGAN SEBAGAI MEDIASI - -, TSALIS KHOLIFATIN ADIL MUTAMIMMAH (Politeknik Caltex Riau, 2024)
This research aims to examine and understand the influence of income levels and locus of control on impulsive buying, with financial literacy as a mediator. This study is a quantitative research employing a questionnaire with a sample size of 149 respondents consisting of civil servants (ASN) across 27 administrative wards in the Tegal City Government. The data analysis technique utilized in this research is Partial Least Squares Structural Equation Modeling (PLS-SEM). The result indicates that income levels and financial literacy exhibit p values > 0,05 indicating no significant influence on impulsive buying, whereas locus of control shows a p values < 0,05 signifying a significant influence on impulsive buying. Financial literacy indirectly mediates the relationship between income levels and impulsive buying as it has a p values > 0,05. However, financial literacy directly mediates the relationship between locus of control and impulsive buying as it has a p values < 0,05. Keywords: Income Levels, Locus Of Control, Financial Literacy, Impulsive Buying